Inflammatory Pain: The Cellular Basis of Heat Hyperalgesia - Huang, Jiehong; Zhang, Xuming; McNaughton, Peter A. (Current Neuropharmacology, 2006)
Injury or inflammation release a range of inflammatory mediators that increase the sensitivity of sensory neurons to noxious thermal or mechanical stimuli. The heat- and capsaicin-gated channel TRPV1, which is an important detector of multiple noxious stimuli, plays a critical role in the development of thermal hyperalgesia induced by a wide range of inflammatory mediators. We review here recent findings on the molecular mechanisms of sensitisation of TRPV1 by inflammatory mediators, including bradykinin, ATP, NGF and prostaglandins. We describe the signalling pathways believed to be involved in the potentiation of TRPV1, and our current understanding of how inflammatory mediators couple to these pathways.
Keywords: TRPV1